Novel Medical and General Hebrew Terminology from the Middle Ages : Volume 5 - Bos, Gerrit (Brill, 2021)
This volume is both a continuation of the four already published titles in the series (2011-19) and an addition to the Concise Dictionary of Novel Medical and General Hebrew Terminology from the Middle Ages . It continues mapping the medical terminology featured in medieval Hebrew medical works in order to facilitate study of medical terms that do not appear in the existing dictionaries, as well as identifying the medical terminology used by specific authors and translators in order to identify anonymous medical material. The terminology discussed in this volume has been derived from fourteen different sources, including translations of Ibn al-Jazzār's Zād al-musāfir by Moses ibn Tibbon ( Sefer Ṣedat ha-Derakhim ) and the otherwise unknown Abraham ben Isaac ( Sefer Ṣedah la-Oreḥim ), as well as the translation of Constantine the Africanʼs Latin version ( Viaticum ) prepared by Do'eg ha-Edomi ( Sefer Yaʾir Netiv ).